The political geography of campaign finance : fundraising and contribution patterns in presidential elections, 2004-2012 /: fundraising and contribution patterns in presidential elections, 2004-2012. (2015) - Mitchell, Joshua, 1955-; Sebold, Karen; Dowdle, Andrew; Limbocker, Scott; Stewart, Patrick A, 1966-
No abstract available